The Integration of Islamic Values in English Classroom in Integrated Islamic School in Mataram Viewed From Teaching Instruments - Imansyah Imansyah; I Made Permadi Utama (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This research was designed as descriptive qualitative research and aimed at figuring out whether or not the Islamic values were integrated with the lesson plan and the syllabus teachers designed. It is essential to see if these values are integrated, considering that JSIT mandates all Islamic schools to incorporate them in all subjects at all levels. The research took place in Mataram, taking English teachers and schools’ curriculum vice principals in four different Islamic integrated schools spread in Mataram as the subjects. Data was collected through document study and interviews. A document study was conducted to see if the Islamic values were added to the indicators and the teaching procedures teachers designed in both the lesson plan and syllabus. A semi-structured interview was carried out with 4 English teachers and 4 curriculum vice principals who were purposively chosen to get more in-depth and comprehensive information on the lesson plan and syllabus they designed. This research suggested that one school successfully implemented integration among the four integrated Islamic schools. This is seen in their indicators and the teaching procedures that reflect Islamic values. The three schools were yet to implement the integration properly as they considered prayers before and after the lesson and some advice during the lesson as the integration.